Infratemporal fossa metastasis of papillary thyroid cancer. Issue 4 (12th April 2012) - Morita, Naruhiko; Morimoto, Koichi; Yonezawa, Koichiro; Otsuki, Naoki; Nibu, Ken‐ichi; Andersen, Peter
Abstract Background Papillary thyroid carcinoma (PTC) occasionally metastasizes to lung and bone, but rarely to skeletal muscles. In this study, we present an unusual case of metastasis of PTC to the infratemporal fossa of a previously treated patient with PTC. Methods and Results A 74‐year‐old man with a diagnosis of PTC underwent subtotal thyroidectomy and neck dissection on the left side. Metastasis to the infratemporal fossa developed 13 years after the initial treatment. The patient underwent extirpation of the tumor via the infratemporal fossa approach with semicoronal skin incision. Right neck dissection and resection of residual thyroid tissue were also performed simultaneously. The patient underwent 131‐Iodine therapy and has been followed up for 12 months with no evidence of disease. Conclusions The possibility of metastasis of PTC should be included as a differential diagnosis if an unusual mass manifests in any location in patients with PTC. © 2012 Wiley Periodicals, Inc. Head Neck, 2013